A clinical case of bovine trypanosomosis in an endemic farm in Malaysia - Jesse, Faez Firdaus Abdullah; Bitrus, Asinamai Athliamai; Abba, Yusuf; Sadiq, Muhammad Abubakar; Hambali, Idris Umar; Chung, Eric Lim Teik; Ping, Frankie Lau Pick; Haron, Abd Wahid; Lila, Mohd Azmi Mohd; Saharee, Abdul Aziz; Norsidin, Mohd Jefri (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: This case report describes the management of a clinical case of trypanosomosis in an adult Friesian Sahiwal cow. Materials and methods: An adult cow aging 3 years was presented with a complain of wound infection, weakness and inappetence. Physical examination was carried out and samples were collected for laboratory investigations. Results: The clinical history revealed generalised enlargements of the pre-scapular and pre-femoral lymph nodes, pale mucous membrane and weight loss. Laboratory investigation showed that the cow had normocytic normochromic anemia with hyperproteinemia. Thin blood smear examination revealed the presence of Trypanosoma evansi. Treatment was instituted with Diminazene aceturate dosed at 3.5 mg/kg bwt through intramuscular (IM) route for 3 days, 20 mL of Fercobsang for 3 days, IM, Flunixin meglumine dosed at 1.1 mg/kg bwt, IM, and Oxytetracycline dosed at 20 mg/kg bwt, IM once. The wounds were cleaned daily for one week. Examination of the blood film after therapy showed no parasite. Conclusion: The findings of this case report demonstrate the importance of an effective treatment regimen in managing bovine trypanosomosis in an endemic farm. http://doi.org/10.5455/javar.2016.c164